Swelling‐Dependent Shape‐Based Transformation of a Human Mesenchymal Stromal Cells‐Laden 4D Bioprinted Construct for Cartilage Tissue Engineering - Díaz‐Payno, Pedro J.; Kalogeropoulou, Maria; Muntz, Iain; Kingma, Esther; Kops, Nicole; D'Este, Matteo; Koenderink, Gijsje H.; Fratila‐Apachitei, Lidy E.; Osch, Gerjo J. V. M.; Zadpoor, Amir A. (Advanced healthcare materials, 2023)
3D bioprinting is usually implemented on flat surfaces, posing serious limitations in the fabrication of multilayered curved constructs. 4D bioprinting, combining 3D bioprinting with time‐dependent stimuli‐induced transformation, enables the fabrication of shape‐changing constructs. Here, a 4D biofabrication method is reported for cartilage engineering based on the differential swelling of a smart multi‐material system made from two hydrogel‐based materials: hyaluronan and alginate. Two ink formulations are used: tyramine‐functionalized hyaluronan (HAT, high‐swelling) and alginate with HAT (AHAT, low‐swelling). Both inks have similar elastic, shear‐thinning, and printability behavior. The inks are 3D printed into a bilayered scaffold before triggering the shape‐change by using liquid immersion as stimulus. In time (4D), the differential swelling between the two zones leads to the scaffold's self‐bending. Different designs are made to tune the radius of curvature and shape. A bioprinted formulation of AHAT and human bone marrow cells demonstrates high cell viability. After 28 days in chondrogenic medium, the curvature is clearly present while cartilage‐like matrix production is visible on histology. A proof‐of‐concept of the recently emerged technology of 4D bioprinting with a specific application for the design of curved structures potentially mimicking the curvature and multilayer cellular nature of native cartilage is demonstrated. 3D bioprinting poses serious limitations in the fabrication of multilayered curved constructs, motivating the development of 4D bioprinting as the next generation of biofabrication technologies. 4D bioprinting, combining 3D bioprinting with time‐dependent stimuli‐induced transformation, enables the fabrication of self‐bending constructs. Here, a 4D smart multi‐material system for curved cartilage engineering is reported as a proof‐of‐concept.